Trafficked Women in Denmark—Falling through the cracks - West, Kira (Anti-Trafficking Review, 2018)
The policy framework for combating human trafficking and protecting victims in Denmark does not match the reality faced by the majority of the migrant women arriving in the country. Especially in relation to women from African countries, the national legislation and regulations can be a source of frustration for agencies such as Reden International, which helps foreign women working in prostitution in Denmark, particularly victims of trafficking.